Investigating family social capital and child health: a case study of South Africa - Abewe, Christabell (Department of Public Health and Family Medicine, 2017)
The link between family social capital and child health has not been well investigated in developing countries. This study assessed socioeconomic inequalities in child health and in family social capital in South Africa. It also assessed the relationship between family social capital and child health. Four waves of the National Income Dynamics Study panel data were used to investigate the relationship between family social capital and child health. Socioeconomic inequalities were assessed using the concentration index. To assess the relationship between family social capital and child health, regressions models were fitted using a selected set of explanatory variables, including an index of family social capital. Child health in this study was operationalized to include: stunting, wasting, and parent-reported health of a child. Results showed that children from the poorest families bear the largest burden of stunting, wasting, and ill health. Similarly, children from poorer households possessed more family social capital when compared to children from more affluent families. Although family social capital was expected to improve child health, the study findings suggest that in South Africa, the socioeconomic status of a family has a greater effect on child health than family social capital.